THE VIEWS OF THE MADURESE KIAI ON THE CONCEPT OF MULTICULTURAL EDUCATION: HISTORICAL, SOCIOLOGICAL, AND PHILOSOPHICAL STUDIES - A. Sa'dud Darain; Zainuddin Syarif; Maimun Maimun; Atiqullah Atiqullah (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This research departs from the dominant tendency in multicultural education studies, which is largely understood as part of modern policies and formal curriculum practices, resulting in models based on religious traditions often being overlooked. In the context of Islamic boarding schools in Madura, kiai not only play a role as teachers, but also as cultural figures, moral leaders, and authoritative sources in shaping attitudes towards diversity, although this dimension has not been widely studied in depth. Therefore, this study aims to analyze how kiai implement multicultural values ​​in daily practice, as well as to uncover the philosophical, historical, and sociological foundations behind them. This study uses a qualitative approach with a phenomenological type to understand the kiai's experiences and views holistically. Data were collected through participant observation, in-depth interviews with three kiai, and documentation studies. Then, they were analyzed using interactive thematic analysis with triangulation techniques to ensure data validity. The results show that multicultural education in Islamic boarding schools is not realized in the form of formal subjects, but is internalized through daily social practices mediated by the kiai's exemplary behavior. The implementation of values ​​is carried out concretely through the application of equality in the dormitory system and discipline, the formation of solidarity through communal living across backgrounds, and the management of conflict in an educational manner through dialogue, advice, and educational sanctions. These practices have been proven to shape the students' tolerance, empathy, and ability to manage differences constructively, while strengthening social cohesion both within the Islamic boarding school environment and the surrounding community. This study concludes that Islamic boarding school-based multicultural education is practical, relational, and rooted in Islamic tradition, thus offering an alternative, contextual and sustainable educational model in building a moderate, inclusive, and harmonious society.